The wmN1 enhancer region in intron 1 is required for expression of human PLP1. Issue 8 (23rd April 2018) - Hamdan, Hamdan; Patyal, Pankaj; Kockara, Neriman T.; Wight, Patricia A.
Abstract: The myelin proteolipid protein gene ( PLP1 ) encodes the most abundant protein present in myelin from the central nervous system (CNS). Its expression must be tightly controlled as evidenced by mutations that alter PLP1 dosage; both overexpression (elevated PLP1 copy number) and lack thereof ( PLP1 deletion) result in X‐linked genetic disorders in man. However, not much is known about the mechanisms that govern expression of the human gene. To address this, transgenic mice were generated which utilize human PLP1 ( hPLP1 ) sequences (proximal 6.2 kb of 5′‐flanking DNA to the first 38 bp of exon 2) to drive expression of a lacZ reporter cassette. Lox P sites were incorporated around a 1.5‐kb section of hPLP1 intron 1 since it contains sequence orthologous to the wmN1 region from mouse which, previously, was shown to augment expression of a minimally‐promoted transgene coincident with the active myelination period of CNS development. Eight transgenic lines were generated with the parental, 6.2hPLP(+)Z/FL, transgene. All lines expressed the transgene appropriately in brain as evidenced by staining with X‐gal in white matter regions and olfactory bulb. Removal of the "wmN1" region from 6.2hPLP(+)Z/FL with a ubiquitously expressed Cre‐driver caused a dramatic reduction in transgene activity. These results demonstrate for the first time that the wmN1 enhancer region: (1) is functional in hPLP1 ; (2) works in collaboration with its native promoter—not just a basal heterologous promoter; (3) is required for high levels of hPLP1 gene activity; (4) has a broader effect, both spatially and temporally, than originally projected with mPlp1 . Main Points: An hPLP1‐lacZ transgene contains sequences sufficient for correct spatiotemporal expression. The wmN1 region within hPLP1 intron 1 is necessary robust expression of hPLP1‐lacZ . The wmN1 enhancer can work in association with its native promoter.